2018
DOI: 10.1021/acs.langmuir.8b01198
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Mechanical Properties of Type III Secretion System EspA Protein by Single Molecule Force Spectroscopy

Abstract: Bacterial pathogens inject virulence factors into host cells during bacterial infections using type III secretion systems. In enteropathogenic Escherichia coli, this system contains an external filament, formed by a self-oligomerizing protein called E. coli secreted protein A (EspA). The EspA filament penetrates the thick viscous mucus layer to facilitate the attachment of the bacteria to the gut-epithelium. To do that, the EspA filament requires noteworthy mechanical endurance considering the mechanical shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…43 Accordingly, the interpretation that the filaments remain intact after their detachment from the AFM tip is highly reasonable as EspA, the T3SS filament building block, unfolds at forces lower than ∼80 pN. 17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Accordingly, the interpretation that the filaments remain intact after their detachment from the AFM tip is highly reasonable as EspA, the T3SS filament building block, unfolds at forces lower than ∼80 pN. 17…”
Section: Resultsmentioning
confidence: 99%
“…Despite these mechanical stresses, the ability to maintain the structural integrity increases the possibility that the long and thin T3SS filament possesses noteworthy mechanical endurance. Although roughly estimated, 17 the hypothesis that the T3SS can sustain its functional-structural properties when subjected to mechanical loads was not yet verified. We have recently studied the biomechanical response of a single EspA subunit to an external load and found that a single EspA protein exhibits relatively low mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…The proteins were purified using HEPES buffer (1.0 mM EDTA, 150 mM NaCl, 20 mM HEPES, pH 7.5) as described elsewhere. 47 …”
Section: Methodsmentioning
confidence: 99%
“…Poly­(I91) octamers were expressed and purified in the laboratory of Dr. Neta Sal-Man at Ben-Gurion University of the Negev, using plasmids that were kindly provided by Prof. J. M. Fernandez from Columbia University. The proteins were purified using HEPES buffer (1.0 mM EDTA, 150 mM NaCl, 20 mM HEPES, pH 7.5) as described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation